Effect of partial replacement of cement with Prosopis juliflora ash on the strength and microstructural characteristics of cement concrete. (20th November 2019) - Kathirvel, Parthiban; Anik, George Amal; Kaliyaperumal, Saravana Raja Mohan
Highlights: PJA is used as partial replacement of cement in the production of cement concrete. Mechanical properties are discussed using compressive strength and impact test. The microstructural properties are discussed using XRD and SEM analysis. Flexural behaviour of reinforced concrete beams is also discussed. Abstract: This paper presents the mechanical and microstructural characteristics of cement concrete with partial replacement of cement with Prosopis juliflora ash (PJA). The fresh property of the mixes was assessed with the help of slump cone test and the mechanical properties such as compressive strength, impact resistance and flexural characteristics of reinforced concrete beams were assessed. From the experimental investigation, it was observed that there were no such appreciable changes in the mechanical properties of the cement concrete when cement is partially replaced with PJA and 20% replacement produces similar mechanical properties of the conventional cement concrete mixes. This results in greater reduction of loss of groundwater due to the growth of PJA as well as reduction in the pollution rate due to effective utilization of PJA and reduced cement production.